Lack of correlation between known virulence properties of Aeromonas hydrophila and enteropathogenicity for humans. - Morgan, D R (1985)
Five strains of Aeromonas hydrophila were selected for use in volunteer challenge trials. All five strains produced cytotoxin, hemolysin enterotoxin, lysine decarboxylase, acetylmethylcarbinol, and DNase. Two strains hydrolyzed esculin. All strains produced purulent hemorrhagic fluid accumulation in rabbit ileal loops, but failed to induce keratoconjunctivitis in guinea pigs. None of the strains produced mannose-resistant hemagglutinins. In challenge studies, diarrhea was demonstrated in only 2 of 57 human volunteers with doses ranging from 10(4) to 10(10) CFU. One person experienced mild diarrhea with 10(9) CFU of strain 6Y. A second person developed moderate diarrhea with 10(7) CFU of strain 3647. At higher doses, no diarrhea was seen in any of the volunteers. The other three strains (B158, SSU, 3284) failed to cause diarrhea and were not recovered from stools of volunteers. Additional virulence properties of A. hydrophila need to be sought before enteropathogenicity for humans can be established.